Building the 'houses of fiction': textual spaces and architectural imagination in Eliza Meteyard's Mainstone's Housekeeper. Issue 6 (3rd June 2022) - Yan, Shu-chuan
ABSTRACT: This article offers a new reading of Eliza Meteyard's fictional writing within the emerging discourse on architecture and design in nineteenth-century Britain. It considers how the format of the novel, Mainstone's Housekeeper (1860), articulates and enforces Meteyard's construction of the textual space as both a narrative and architectural endeavour. I argue that the conceptual idea of literary architecture provides a metaphorical lens through which to understand the analogy between building and writing, architecture and text. I also maintain that Meteyard's construction of her fictional houses in Mainstone's Housekeeper supports the theories that posit a link between interrelated notions of theatricality and interiority. My article first explores how Meteyard's literary representations of decorative arts and architectural design became a deciding component in the development of her writing career. It, then, considers how Meteyard employs the fictional form of Mainstone's Housekeeper to describe Miss Eliot's endeavours to reform Mr. Radnor's domestic affairs through her disguised identity. While Mr. Radnor's poor management of his household creates the senses of male captivity and bleak emptiness, Miss Eliot's redecorating project, nonetheless, reinforces her performance as an architect-designer, an embodiment of female authority in the domestic sphere.